The influence of the volume fraction of meat in dumplings on their cooking time - V. N. Makarov; A. R. Sadykov; D. C. Chetverikova (Пищевые системы, 2024)
Based on the studied literature, the aim was to investigate the influence of the volume fraction of meat in meat dumplings (pelmeni) and the number of dumplings on their cooking time, as well as to analyze the physico-mathematical and technical aspects to be taken into account (or not) within the framework of the planned experiment. To achieve this goal, the following tasks were set: to conduct experimental studies, to describe the assumptions that need to be accepted when performing the study and to conduct theoretical studies (numerical experiments, using the finite element method). When conducting experiments, dumplings of well-known brands, the names of which were conventionally labeled as “SK”, “SZ”, “RE”, “TS”, were chosen as objects of research. The need to study the dumplings of well-known brands is justified by both consumer interest and a smaller variability of product parameters, which increases the reproducibility of the results of the study. As assumptions adopted in real experiments, the authors emphasize the following ones: distilled water is used in cooking, the volume of a dumpling does not change during cooking, the biochemical composition of the filling can be neglected. As a result of the theoretical analysis, the following assumptions were made: the study of dumpling cooking does not take into account the resistance forces, i. e., turbulent and convective flows, as well as thermo-elastic effects; the time of dumpling floating to the surface is negligibly small; "approximation of initial values" — geometric, physico-chemical parameters of the dumpling do not change during cooking. Cooking time of 1, 5, 10 dumplings of known brands was obtained on the basis of numerical experiments. Using real experiments, the time from immersion of the dumplings in water to their floating to the surface was investigated. As a result of numerical experiments it has been found that the time of heating the center of the dumpling of known brands to the temperature of protein denaturation differs from the time of floating to the surface by about 360 seconds. Consequently, after floating to the surface, the dumplings of known brands need about six more minutes of cooking time until they are fully cooked.